Studi Karakteristik Variasi Jumlah Sudu Impeler Pada Unjuk Kerja Blower Sentrifugal - K Umurani1; Habiburrahman Habiburrahman (Fakultas Teknik UMSU, 2019)
Blower is a device that is often used because it is able to increase or add gas that will be flowed in a particular room as well as suctioning or vacuuming gas. At present the blower is comprehensive, starting from laboratories, office buildings and industries which are widely used as a component in the production process. There are several classifications of blowers, namely centrifugal blowers which include radial blade, forward curve blade and backward curve blade. Then, the positive displacement blower includes the vane blower. This study aims to determine the performance of centrifugal blowers when adding the number of blades to the centrifugal impeller blower. There are 3 impellers that are used with variations in the number of different blades, 6, 8, and 10 in testing to find the performance of centrifugal blowers. Air speed is measured using an anemometer while pressure drop measured using a manometer U pipe containing oil fluid. The number of blade impeller affect the increasing performance of blower.